Analisis Diskursus Pemerataan Ekonomi dalam Pembangunan Nasional Ibu Kota Nusantara - Desfiandri Rahmadani Amri; Zulkipli Lessy (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The discourse regarding economic equality in the development of the Indonesian Capital City (IKN), focuses on key aspects such as infrastructure, environmental sustainability, economic regulations, and empowerment of local communities. Through discourse analysis methods, this research explores the narratives and language used by stakeholders regarding IKN projects in the context of infrastructure, environmental sustainability aspects, economic regulations. empowering local communities By analyzing discourse related to the IKN project, this research seeks to provide in-depth insight into how economic equality is integrated into IKN development. The implications of these findings can be used as a guide for planning and implementing similar projects in the future.